Evaluation of physical activity levels among medical students at unjani medical school - Y Triningtyas, Anastasia; Afrila, Syafarina (ACTA Medical Health Sciences, 2024)
Physical activity is essential for the health and professional development of medical students. Previous studies have indicated that the level of physical activity among medical students is generally low, with up to 60% being inactive. Technological advancements and the predominantly sedentary nature of medical education contribute to these low daily activity levels, leading to a tendency toward an inactive lifestyle. On the other hand, medical students, as future healthcare providers, play a crucial role in encouraging their patients to adopt healthy physical activity habits. This study aims to evaluate the physical activity levels of students at the Faculty of Medicine at Universitas Jenderal Achmad Yani (UNJANI). Using observational design, this cross-sectional study involved a total of 60 respondents from the Medical Education Program who met the research criteria and were selected through consecutive sampling. Data regarding age, gender, and physical activity were collected using a questionnaire. Physical activity was measured using the standardized long-form International Physical Activity Questionnaire (IPAQ). The results show that the majority of students had a moderate level of physical activity (45%), followed by low (28.3%) and high levels (26.7%). The proportion of female respondents with low physical activity levels was significantly higher (36.8%) compared to males (13.6%). Among female participants, physical activity levels were predominantly categorized as low and moderate, whereas male participants displayed a higher distribution of moderate and high activity levels. These results highlight the necessity for targeted interventions to promote physical activity, particularly in encouraging a healthier lifestyle among medical students at UNJANI. DOI : 10.35990/amhs.v3n2.p60-67 REFERENCES Organización Mundial de la Salud. Global Status Report on Physical Activity 2022 [Internet]. WHO Press; 2022. 1–112 p. Available from: https://www.who.int/teams/health-promotion/physical-activity/global-status-report-on-physical-activity-2022 Dinas Kesehatan. Laporan Riskesdas 2018 Nasional. Lembaga Penerbit Balitbangkes; 2018. Riskawati YK, Prabowo ED, Al-Rasyid H. Physical Activity Level of the Second, Third, and Fourth Years Students at Study Program of Medicine. Majalah Kesehatan Fakultas Kedokteran Universitas Brawijaya. 2018;5(1):26–32. Utomo HS, Handayani S, Wiyono N. Hubungan Aktivitas Fisik dengan Kapasitas Memori Kerja pada Mahasiswa Program Studi Kedokteran Universitas Sebelas Maret. Nexus Kedokteran Komunitas. 2016;5(2):1–11. Analysis of the International Physical Activity Questionnaire (IPAQ). Acta Crystallographica Section E. 2005;68(9):1–15. Seeveldt V, Malina RM, Clark MA. Factors Influencing Levels of Physical Activity in Adults. Sports Medicine. 2002;32(3):143–68. World Health Organization. WHO Guidelines on Physical Activity and Sedentary Behaviour. Routledge Handbook of Youth Sport; 2016. Kementerian Kesehatan RI. Ayo Bergerak, Lawan Obesitas. 1st ed. Sulistyowati LS, editor. Jakarta: Kemenkes; 2017. p. 2–6. Wicaksono A, Handoko W. Aktivitas Fisik dan Kesehatan [Internet]. Pontianak: IAIN Pontianak Press; 2021. p. 32–36. Available from: https://www.researchgate.net/publication/353605384 Lorenza A, Machrina Y. Dengan Derajat Dismenore Primer pada Mahasiswi Universitas Muhammadiyah Sumatera Utara. Anastasia Y Triningtyas, et al. Farradika Y, Umniyatun Y, Nurmansyah MI, Jannah M. Perilaku Aktivitas Fisik dan Determinannya pada Mahasiswa Fakultas Ilmu-Ilmu Kesehatan Universitas Muhammadiyah Prof. Dr. Hamka. ARKESMAS (Arsip Kesehatan Masyarakat). 2019;4(1):134–42. Pratama A, Zulfahmidah Z. Gambaran Indeks Massa Tubuh (IMT) pada Mahasiswa. Indonesian Journal of Health. 2021;2(01):1–7. Angesti AN, Manikam RM. Faktor yang Berhubungan dengan Status Gizi Mahasiswa Tingkat Akhir S1 Fakultas Kesehatan Universitas MH Thamrin. Jurnal Ilmiah Kesehatan. 2020;12(1):1–14. Annamayra A, Ramli RS, Nur L. Gambaran Tingkat Aktivitas Fisik Mahasiswa Fakultas Kedokteran Universitas Pasundan di Era New Normal. Jurnal Maenpo: Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi [Internet]. 2022;12(2):206–18. Available from: https://jurnal.unsur.ac.id/maenpo Hidayat A, Suroto. Hubungan antara Status Gizi dan Aktivitas Fisik dengan Tingkat Kebugaran Jasmani Siswa. Jurnal Pendidikan Olahraga dan Kesehatan. 2016;4(2):516–21. Alkaririn MR, Aji AS, Afifah E. Hubungan Aktivitas Fisik dengan Status Gizi Mahasiswa Keperawatan Universitas Alma Ata Yogyakarta. 2022;5:146–51. Habut MY, Nurmawan IPS, Wiryanthini IAD. Hubungan Indeks Massa Tubuh dan Aktivitas Fisik terhadap Daya Tahan Kardiovaskular pada Mahasiswa Fakultas Kedokteran Universitas Udayana. Erepo Unud. 2015;831:1–14. Herazo-Beltrán Y, Pinillos Y, Vidarte J, Crissien E, Suarez D, García R. Predictors of Perceived Barriers to Physical Activity in the General Adult Population: A Cross-sectional Study. Brazilian Journal of Physical Therapy [Internet]. 2017;21(1):44–50. Available from: http://dx.doi.org/10.1016/j.bjpt.2016.04.003 Schlickmann DW, Kock KS. Level of Physical Activity Knowledge of Medical Students in a Brazilian University. Journal of Lifestyle Medicine. 2022;12(1):47–55. World Health Organization. Global Recommendations on Physical Activity for Health [Internet]. 2018. Available from:http://link.springer.com/10.1007/978-3-319-59379-1http://dx.doi.org/10.1016/B978-0-12-420070-8.00002-7http://dx.doi.org/10.1016/j.ab.2015.03.024https://doi.org/10.1080/07352689.2018.1441103http://www.chile.bmw-motorrad.cl/sync/showroom/lam/es/ Medagama A, Galgomuwa M, De Silva C. Physical Activity Patterns and Socio-demographic Correlates of Physical Activity Among Medical Undergraduates in Sri Lanka: An Observational Study. Postgraduate Medical Journal. 2018;94(1107):32–6. Uğraş Dikmen A, Altunsoy M, Koç AK, Koç E, Özkan S. Physical Activity Level of Medical Students: Is There a Family Effect? Current Medical Research. 2022;3(November):68–73. Mohammed G, Md Said S, Azuhairi, Ariffin A, Kamaruzaman J. Physical Inactivity and Its Associated Factors Among University Students. IOSR Journal of Dental and Medical Sciences. 2014;13(10):119–30. Worobetz A, Retief PJ, Loughran S, Walsh J, Casey M, Hayes P, et al. A Feasibility Study of an Exercise Intervention to Educate and Promote Health and Well-being Among Medical Students: The “MED-WELL” Programme. BMC Medical Education. 2020;20(1):1–12.